(untitled) - Folds, Victoria; Victoria Folds (Clifton Park, NY, 2008)
Three-Step Tray Tasking: Prompting Young Children's Emerging Organizational Thinking Skills is an innovative text that provides an easy approach to helping young children develop their organizational thinking skills. Using three "trays" that represent a task's beginning, middle and end helps to develop these important skills. Emphasis is placed on small motor refinement and critical thinking skills as children move through a variety of tracing to cutting to assemblage tasks. This text captures a child's interest in working through logical steps toward the completion of a project, challenging their ability to concentrate and attend to a task as well as practicing grasping and controlling tools. Three-Step Tray Tasking offers teachers the opportunity to observe and record authentic assessment as children move through three steps that reveal their ability to handle materials appropriately, complete each stage correctly and develop logical thinking habits. This text reinforces the importance of providing three, four and five year olds the opportunity to engage in meaningful, satisfying work
Includes bibliographical references
Keywords: Early childhood education; Early childhood education; Education; Preschool; Creative activities and seat work